My new home? : Strategies and challenges of refugee integration programs in Portugal - Constantino, Catarina (2022)
Europe is experiencing the greatest humanitarian crisis since the Second World War, which is reflected in an unprecedented influx of refugees into Europe. Against this backdrop, the effective strategies and challenges faced by the programs designed to facilitate the integration of refugees need to be understood. Portugal, together with other countries, has opened its doors to refugees. In this study, qualitative methods are used to understand how the refugee reception and integration are being conducted in Portugal. The perspectives of both refugees and professionals involved in programs aimed at promoting the integration of refugees are taken into consideration. The results suggest that, despite the existence of best practices in the various types of programs, there is significant room for improvement. Thus, specific changes to these programs are proposed with a view to boosting their efficacy and facilitating the integration of refugees in Portugal.